THE EFFECT OF ADDING BLUE SWIMMING CRAB SHELL FLOUR ON INCREASING CALCIUM AND THE PREFERENCE LEVEL FOR BISCUIT - Annisa Dewi Nur Azizia; Evi Liviawaty; Ayi Yustiati; Rusky Intan Pratama (Jurnal Perikanan Unram, 2024)
Blue Swimming Crab (Portunus pelagicus) has a calcium content of 19.97% which can be fortified in biscuit products. The purpose of this study was to understand the impact of using crab shell flour in biscuits on panelist preferences. The study was conducted from July to August 2024 at the Fisheries Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University. The method used in this study was experimental using Friedman data analysis consisting of 4 treatments and 20 replications in the form of semi-trained panelists on organoleptic parameters, namely appearance, aroma, taste, and texture and chemical parameters, namely calcium content, water content, ash content, protein content, fat content, and carbohydrate content. The results of the hedonic test proved that the addition of 5% crab shell flour was the most preferred treatment, with an average appearance value of 7.9; aroma 8.2; taste 8.1; and texture 8.1. Based on chemical analysis of the most preferred treatment, namely the addition of 5% crab shell flour produced a calcium content of 1.98%; water content 2.11%; ash content 3.45%; protein content 12.35%; fat content 9.91%; and carbohydrate content 72.18%.